(untitled) - Peters, Michael H. (New York, 2005)
Many newly developing fields of science and engineering, including nanotechnology, protein engineering, microfluidics, etc., require an in-depth molecular understanding and description of matter. Molecular Thermodynamics and Transport Phenomena: Complexities of Scales in Space and Time provides a rigorous molecular and statistical mechanical basis for the classical fundamental molecular description of matter. The author uniquely explores the disparities in spatial and temporal time scales in molecular mechanical dynamics and interactions that lead to the different observed behavior of matter, including equilibrium vs. nonequilibrium behavior, phase states, and irreversibility. This book provides a modern, comprehensive foundation for the classical molecular theory of matter that is demanded of today’s advancing fields of science and technology.
Keywords: Thermodynamic equilibrium,Transport theory,Space and time,Mechanics; Textbooks